Parenting and Family Diversity Issues - Lang, Diana (Open textbook library., 2020)
This book has been created for students and all individuals who work with children and families (e.g., educators, parents, caregivers, direct support workers, etc.) in diverse contexts. It is imperative to understand how and what factors may influence child outcomes across the lifespan. Therefore, key concepts related to parenting, child-rearing, care-giving, and parenting education are outlined in this textbook to provide historical, theoretical, and practical perspectives across vast settings and developmental domains.